The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1093/hmg/ddl053
|View full text |Cite
|
Sign up to set email alerts
|

Nell1-deficient mice have reduced expression of extracellular matrix proteins causing cranial and vertebral defects

Abstract: The mammalian Nell1 gene encodes a protein kinase C-beta1 (PKC-beta1) binding protein that belongs to a new class of cell-signaling molecules controlling cell growth and differentiation. Over-expression of Nell1 in the developing cranial sutures in both human and mouse induces craniosynostosis, the premature fusion of the growing cranial bone fronts. Here, we report the generation, positional cloning and characterization of Nell1(6R), a recessive, neonatal-lethal point mutation in the mouse Nell1 gene, induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
121
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 37 publications
4
121
1
Order By: Relevance
“…It has also been reported that overexpression of NELL1 promotes apoptosis in osteoblasts both in vitro and in vivo (Zhang et al, 2003), and that this apoptotic activity may be associated with the Fas signaling pathway (Zhang et al, 2006). In NELL1 6R mutant mice, loss of NELL1 expression was associated with reduced expression of genes encoding tumor necrosis factor receptor superfamily member 11b and extracellular matrix proteins (Desai et al, 2006), which have also been implicated in human carcinogenesis (Ingber, 2002;Rowinsky, 2005). Furthermore, the high frequency (44%) of NELL1 promoter hypermethylation in colon cancer suggests a potential role for NELL1 inactivation in colon tumorigenesis (Mori et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has also been reported that overexpression of NELL1 promotes apoptosis in osteoblasts both in vitro and in vivo (Zhang et al, 2003), and that this apoptotic activity may be associated with the Fas signaling pathway (Zhang et al, 2006). In NELL1 6R mutant mice, loss of NELL1 expression was associated with reduced expression of genes encoding tumor necrosis factor receptor superfamily member 11b and extracellular matrix proteins (Desai et al, 2006), which have also been implicated in human carcinogenesis (Ingber, 2002;Rowinsky, 2005). Furthermore, the high frequency (44%) of NELL1 promoter hypermethylation in colon cancer suggests a potential role for NELL1 inactivation in colon tumorigenesis (Mori et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…The NELL1 gene encodes a protein kinase C-binding protein that contains six EGF-like domains and belongs to a new class of cell-signaling molecules controlling cell growth and differentiation (Matsuhashi et al, 1995;Watanabe et al, 1996;Kuroda and Tanizawa, 1999;Desai et al, 2006). The precise roles of NELL1 in Hypermethylation of NELL1 in esophageal cancer Z Jin et al physiology and pathophysiology remain incompletely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…24,89 In support of this concept, mice homozygous for Nell1 deficiency exhibit reduced expression of the osteoclastogenesis inhibitor osteoprotegerin, 6 and the heterozygous Nell1-deficient mice that survive to adulthood manifest an osteoporotic phenotype. 39 Interestingly, BMP2 and Wnt signaling synergistically increase osteoprotegerin expression, 90 and ongoing studies will determine whether BMP2þNELL-1 can similarly induce osteoprotegerin and/or inhibit osteoclastogenesis.…”
Section: Nell-1 Enhances Bmp2 Osteogenesismentioning
confidence: 96%
“…(13) In addition, Nell-1 overexpression results in abnormal cartilage formation, (14) whereas loss of Nell-1 function results in reduced gene expression of extracellular matrix proteins critical for osteogenesis and chondrogenesis. (15) In this study we revealed roles for Nell-1 in the molecular regulation of chondrogenesis using ATDC5 cells, a murine embryonal carcinoma-derived chondroprogenitor cell line that undergoes a multistep chondrogenic differentiation process beginning with mesenchymal condensation and culminating in cartilage formation in vitro. (16,17) The ATDC5 cell line is a commonly used model for dissecting molecular mechanisms underlying the regulation of chondrocyte differentiation during endochondral bone formation.…”
Section: Introductionmentioning
confidence: 95%
“…Nell1-deficient neonatal mice (15) and wild-type littermates were euthanized and fixed in 10% formalin, and femurs were isolated and embedded in paraffin. Mouse embryos were collected from pregnant C57BL/6 mice, where age was defined as E0.5 on the day the vaginal plug was observed.…”
Section: Immunohistochemistrymentioning
confidence: 99%